2022
DOI: 10.21203/rs.3.rs-2162558/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence that earthworms increase soil greenhouse gas emissions (CO 2 and N 2 O) in the presence of plants and soil moisture fluctuations

Abstract: Earthworms can stimulate plant productivity, but their impact on soil greenhouse gases (GHG) is still debated. Methodological challenges of measuring GHG in experiments with plants are presumably contributing to the status quo, with the majority of studies being conducted without plants. Here we report the effect of earthworms (without, anecic, endogeic and their combination) and plants (with and without) on GHG (CO2 and N2O) emissions in an experiment. N2O emissions were also 34.6 and 44.8% lower when both ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 63 publications
(50 reference statements)
5
4
0
Order By: Relevance
“…In a more recent eld study (upland rice), John et al 39 showed that earthworms did not affect CO 2 emissions over the whole rice growing season but that they did have an effect depending on the rice growth stage. Last, but not least, the results are in line with the ndings of Ganault et al 15 , performed on the same soil and using a subset of the same earthworm species in a mesocosm experiment with plants, which showed no signi cant effect of earthworms on soil CO 2 emissions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In a more recent eld study (upland rice), John et al 39 showed that earthworms did not affect CO 2 emissions over the whole rice growing season but that they did have an effect depending on the rice growth stage. Last, but not least, the results are in line with the ndings of Ganault et al 15 , performed on the same soil and using a subset of the same earthworm species in a mesocosm experiment with plants, which showed no signi cant effect of earthworms on soil CO 2 emissions.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the presence endogeic earthworms let to a statistically marginal reduction of N 2 O emissions in the wheat (-48.6%) and intercrop_1 period (i.e., between wheat and mustard) and a similar trend was noted for the mustard and maize crops. These ndings are in agreement with Ganault et al 15 study, which reported a signi cant reduction in N 2 O emissions in mesocosm experiments with the same soil type when the endogeic species A. icterica was present. Similar to Ganault et al 15 , we also identi ed transient N 2 O stimulation during some periods of the experiment, but overall, these effects were not signi cant when integrating over the entire duration of the experiment.…”
Section: Earthworm Effects On N 2 O Emissionssupporting
confidence: 93%
See 3 more Smart Citations